COMBINING ABILITY AND HETEROSIS OVER LOCATIONS FOR YIELD AND YIELD COMPONENTS IN HYBRID RICE (Oryza sativa L.) - BALRAM; L. KRISHNA, T. VIRENDER JEET SINGH, CH. DAMODAR RAJU, Y. CHANDRA MOHAN (The Journal of Research, PJTSAU, 2021)
A set of 32 newly developed hybrids along with their parents (B and R lines) and standard checks viz., RNR 15048 and PA 6444 were evaluated for thirteen grain yield and its contributing traits to estimate heterosis and combining ability effects in rice through Line × Tester analysis. The mean performance of hybrids for most of the characters was higher than that of parents except for milling percent. The analysis of variance revealed significant differences among parents, lines and hybrids for most of the characters studied. Degree of dominance was less than unity for days to 50 percent flowering, plant height, panicle length, panicle weight, 1000 grain weight, number of filled grains per panicle and spikelet fertility indicating the existence of partial dominance. SCA variances were higher than GCA variances for most of the characters, which indicated the predominance of non-additive gene action. The gca effects revealed that the line JMS 14B and three testers viz., RNR 26059, RNR 26072 and PAU 2K10-23-451-2- 37-34-0-3 were found to be good general combiners for yield and majority of the yield contributing traits in desirable direction. Of the thirty two hybrids, JMS 14A × RNR 26083, JMS 14A × RNR 26084, CMS 64A × PAU 2K10-23-451-2-37-34-0-3, CMS 23A × RNR 26072 and CMS 64A × RNR 26059 were found good specific combiners. Eight and five hybrids had positive and significant standard heterosis over varietal check (RNR 15048) and hybrid check (PA 6444), respectively. Based on sca and heterosis, hybrids JMS 14A × RNR 26083, JMS 14A × RNR 26059, CMS 64A × PAU 2K10-23-451-2-37-34-0-3, CMS 23A × RNR 26072 and CMS 64A × RNR 26059 were found promising for further exploitation.